2011
DOI: 10.1016/j.cemconres.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics analysis of thermal expansion and thermal pressurization of a hardened cement paste

Abstract: The results of a macro-scale experimental study of the effect of heating on a fluid-saturated hardened cement paste are analysed using a multi-scale homogenization model. The analysis of the experimental results revealed that the thermal expansion coefficient of the cement paste pore fluid is anomalously higher than the one of pure bulk water. The micromechanics model is calibrated using the results of drained and undrained heating tests and permits the extrapolation of the experimentally evaluated thermal exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 42 publications
3
22
0
1
Order By: Relevance
“…A comparison with the results presented in Figure 3 shows that the effective thermal expansion coefficient of the hardened cement paste should decrease with porosity increase. This is compatible with the experimental results of Zeng et al (2012) and also with the results of the micromechanics modellings of Ghabezloo (2011) which show the reduction of the drained thermal expansion coefficient with the porosity increase for cement pastes with different water-to-cement ratios.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…A comparison with the results presented in Figure 3 shows that the effective thermal expansion coefficient of the hardened cement paste should decrease with porosity increase. This is compatible with the experimental results of Zeng et al (2012) and also with the results of the micromechanics modellings of Ghabezloo (2011) which show the reduction of the drained thermal expansion coefficient with the porosity increase for cement pastes with different water-to-cement ratios.…”
Section: Figuresupporting
confidence: 91%
“…In a simplified view, a completely hydrated cement paste can be seen as a mixture of C-S-H, Portlandite (CH) and porosity. The thermo-elastic properties of the C-S-H solid are not clearly known, however an indirect estimation of these parameters has been done by Ghabezloo ( , 2011 by the back analysis of the results of macro-scale experimental study of Ghabezloo et al (2008) using a micromechanics model. The bulk modulus and volumetric thermal expansion coefficient of the C-S-H solid have been evaluated respectively equal to 25 GPa and 42 × 10 −6 ( • C) −1 .…”
Section: Figurementioning
confidence: 99%
“…microthermoporomechanics backanalysis [70]. The CSH density is found to decrease with increasing Ca∶Si ratio, 2.55 g=cm 3 > ρ CSH > 2.35 g=cm 3 .…”
Section: Nanoscale Heat-capacity Calculationsmentioning
confidence: 87%
“…In a similar approach, Sun and Scherer (2010a and b) excluded the volume of interlayer water in their evaluation of the active porosity of mortar samples. Ghabezloo et al (2008) and Ghabezloo (2010 and2011) also demonstrated that only a proportion of the total porosity of cement, corresponding to the mercury intruded porosity, was to consider when dealing with its poroelastic response. This extension to claystones of findings on other porous material in which mineral/water interactions are also significant confirms the similarity between both materials.…”
Section: Biot Effective Stress Coefficientsmentioning
confidence: 99%